2016
DOI: 10.3329/baj.v18i2.28906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen on Weed Infestation and Performance of Boro Rice Under Two Selected Herbicides

Abstract: A field experiment was conducted at the experimental farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur from November 2013 to May 2014 to determine the effect of nitrogen and herbicide on weed infestation and performance of Boro rice (cv. BRRIdhan28). Five nitrogen doses i.e. 0 , 50.6 , 101.2 , 151.8 and 202.4 kg ha-1 under selected pre-emergence and post-emergence herbicides along with one weed free and control (unweeded) treatment were imposed in the experiment. Nine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Kumar et al,(2013) reported that among various herbicides, application of Pretilachlor 750 g ha -1 (pre-emergence) fb Azimsulfuron 35 g ha -1 + NIS (0.25%) at 15 DAT recorded significantly highest net returns (27,461 ha-1) and B:C ratio (1.32). Morshed et al,(2015) found that application of Pyrazosulfuron ethyl @ 150 g ha -1 at 15 DAS + N @ 202 kg ha -1 fetched highest gross and net returns whereas, maximum B: C ratio in Pyrazosulfuron ethyl @ 150g ha -1 at 15 DAS + N @ 151.8 kg ha -1 . Prashanth et al, (2016) reported that among the different herbicide treatments, application of Bispyribac Na @ 25 g ha -1 at 15 DAT has recorded maximum net returns and B:C ratio fb Bensulfuron-methyl + Pretilachlor @ 10 g ha -1 at 8 DAT.…”
Section: Yield Attributes and Yieldsmentioning
confidence: 92%
See 2 more Smart Citations
“…Kumar et al,(2013) reported that among various herbicides, application of Pretilachlor 750 g ha -1 (pre-emergence) fb Azimsulfuron 35 g ha -1 + NIS (0.25%) at 15 DAT recorded significantly highest net returns (27,461 ha-1) and B:C ratio (1.32). Morshed et al,(2015) found that application of Pyrazosulfuron ethyl @ 150 g ha -1 at 15 DAS + N @ 202 kg ha -1 fetched highest gross and net returns whereas, maximum B: C ratio in Pyrazosulfuron ethyl @ 150g ha -1 at 15 DAS + N @ 151.8 kg ha -1 . Prashanth et al, (2016) reported that among the different herbicide treatments, application of Bispyribac Na @ 25 g ha -1 at 15 DAT has recorded maximum net returns and B:C ratio fb Bensulfuron-methyl + Pretilachlor @ 10 g ha -1 at 8 DAT.…”
Section: Yield Attributes and Yieldsmentioning
confidence: 92%
“…Sudeshna et al,(2014) results revealed that maximum grain yield was recorded in 2 HW at 20 and 40 DAT and it was fb HW at 20 DAT along with Oxadiargyl @ 0.1 kg -1 . Morshed et al, (2015) reported that application of Pyrazosulfuran ethyl (150 g ha -1 ) at 15 DAT along with N @ 200.4 kg ha -1 showed higher no. of tiller hill -1 , total dry matter, panicle hill -1 , filled grains panicle -1 (125.20) and grain yield (6.46 t ha -1 ).…”
Section: Weed Management Practices In Boro Ricementioning
confidence: 99%
See 1 more Smart Citation